De Brabantse Omwenteling en de Verenigde Nederlandse Staten (1789-1790). - Bernard, Bruno; Maskens, Robert (Brussel : Museum van de stad Brussel, 2003)
Bibliotheek François Vercammen
Nederlands
Monografie